STUDI EFEKTIFITAS PENGGUNAAN JEJARING SOSIAL SEBAGAI PENUNJANG PROSES PEMBELAJARAN PADA MAHASISWA FAKULTAS TEKNOLOGI INFORMASI DAN KOMUNIKASI USM - Robby Kurniawan Budhi; Vensy Vydia; Maya Rini Handayani (Jurusan Teknologi Informasi Universitas Semarang, 2011)
Social network developing as medium of communication was effloresce quick. Accompanying sites as Facebook have become tren and one wills be main requirement for one any one. And so do thing it among civitas Technological Faculty academic person Information and semarang University Communication (FTIK USM). Among college student, Facebook is accessed everyday and bermunculan's community group. One of it is group